High-pressure processing influences the conformation, water distribution, and gel properties of pork myofibrillar proteins containing Artemisia sphaerocephala Krasch gum - Shengming Zhao; Zhao Li; Yu Liu; Yanan Zhao; Xiaorui Yuan; Zhuangli Kang; Mingming Zhu; Hanjun Ma (Food Chemistry: X, 2022)
The effect of high-pressure processing (100–4 00 MPa) on conformation, water distribution, and gel characteristics of reduced-sodium (0.3 M NaCl) myofibrillar protein containing 0.15% Artemisia sphaerocephala Krasch gum (AG) was investigated. The addition of AG resulted in the increase of WHC, proportion of immobilized water, and gel strength. Then, the WHC, proportion of immobilized water, and gel strength peaked after 200 MPa treatment, attributed to increased solubilization and zeta potential of MP, decreased particle size of MP, exposure of intrinsic tryptophan residues and the partial transformation of α-helix into β-sheet in MP. Moreover, 300 and 400 MPa induced decreases in surface hydrophobicity, solubility and storage modulus, resulting in the formation of loose and disordered gel structures with attenuated WHC. These results suggest that application of moderate HPP (200 MPa) combined with AG could provide a novel approach to improve the WHC and gelation properties of reduced-sodium meat products.